New Mobile Marketing Capabilities of the Android Platform - Gurgul, Piotr (Managerial Economics, 2012)
Rapid development of the intelligent mobile devices such as smartphones and tablets created numerous opportunities for new forms of both mobile marketing and marketing in general. The emergence of smartphones complies with the drive for new ways of targeted and measur- able marketing as proposed by integrated marketing communication paradigm. New technical features such as barcode scanners, QuickResponse codes, AGPS or Near Field Communication (NFC) enable high level of personalization and engagement. The Android platform additionally increases the potential of smartphone marketing. The aim of this paper is to explore new technical features available in Android 4.0 Ice Cream Sandwich and investigate their potential use in mobile marketing. The emphasize is put on the special role that NFC may play in the marketing of the future. Besides, the significant part of the paper is committed to existing ways of marketing using smartphone and indicating the superiority of Android over other platforms in terms of results.